PTHrP treatment of colon cancer cells promotes tumor associated-angiogenesis by the effect of VEGF - Calvo, Natalia Graciela (2019)
We showed that Parathyroid Hormone-related Peptide (PTHrP) induces proliferation, migration, survival and chemoresistance via MAPKs and PI3K/AKT pathways in colorectal cancer (CRC) cells. The objective of this study was to investigate if PTHrP is also involved in tumor angiogenesis. PTHrP increased VEGF expression and the number of structures with characteristics of neoformed vessels in xenografts tumor. Also, PTHrP increased mRNA levels of VEGF, HIF-1α and MMP-9 via ERK1/2 and PI3K/Akt pathways in Caco-2 and HCT116 cells. Tumor conditioned media (TCMs) from both cell lines treated with PTHrP increases the number of cells, the migration and the tube formation in the endothelial HMEC-1 cells, whereas the neutralizing antibody against VEGF diminished this response. In contrast, PTHrP by direct treatment only increased ERK1/2 phosphorylation and the HMEC-1 cells number. These results provide the first evidence related to the mode of action of PTHrP that leads to its proangiogenic effects in the CRC.